Hypnotherapy and Emotional Freedom Technique (EFT) Interventions on Mental Health of Students at SMAN 68 Jakarta - Arditiyanto, Muhamad Andri Hakim; Cicih , Lilis Heri Mis; Jumhati , Siti (LPPM Universitas Mohammad Husni Thamrin, 2026)
Student anxiety has become an increasing mental health concern that may negatively affect academic performance and psychological well-being. Complementary psychological interventions offer promising alternatives to reduce anxiety in school settings. This study aimed to analyze the effectiveness of hypnotherapy, Emotional Freedom Technique (EFT), and their combination in reducing students’ anxiety levels. A quasi-experimental design with a pretest–posttest control group approach was employed. The sample was divided into four groups: hypnotherapy, EFT, combination, and control group. Anxiety levels were measured using the Generalized Anxiety Disorder-7 (GAD-7). Data were analyzed using paired sample t-tests and comparative tests between groups. The results showed that the hypnotherapy, EFT, and combination groups experienced statistically significant reductions in GAD-7 scores (p < 0.001) with large effect sizes, whereas the control group showed no significant change (p > 0.05). No significant differences were found among the three intervention methods. In conclusion, hypnotherapy, EFT, and their combination are effective in reducing students’ anxiety levels and have potential to be implemented as school-based mental health interventions.